Algebraic condition for decomposition of large-scale linear dynamic systems - Górecki, Henryk (1927-2022) (Zielona Góra: Uniwersytet Zielonogórski)
The paper concerns the problem of decomposition of a large-scale linear dynamic system into two subsystems. An equivalent problem is to split the characteristic polynomial of the original system into two polynomials of lower degrees. Conditions are found concerning the coefficients of the original polynomial which must be fulfilled for its factorization.
Keywords: decomposition; algebraic condition; dynamic systems